EFFECT OF POC MADE FROM MACKEREL FISH WASTE TOWORD THE GROWTH AND YIELD OF PEANUT PLANT ON PEAT SOIL - Sasni, Nurjani, Maulidi, Yam (Jurnal Sains Mahasiswa Pertanian, 2019)
The objectives of this research were to observe concentration of the best POC mackerel fish waste for growth and yield of peanut plant on peat soil. The reseach was carried from 16 September 2018 to 9 Desember 2018 at the experimental of Faculty of Agriculture Univercity of Tanjungpura. This study used a Completely Rendomized Design of 5 treatments with 4 replication each and replication consists of 4 samples. The treatment consisted of 10ml/L water; 20ml/L water; 30ml/L water; 40ml/L water; 50ml/L air. The observed variables this study include high plant, dry weight plant (cm), wet weight pods (g), number pods (g), amount seed contens, number empty seeds and seed dry weight (g). Result based of the research on conducted, concentrations of POC mackerel fish waste effectively domonstrated by peanut plant with a cpncentration of 10 ml/L water.Â Keywords : mackerel fish waste POC, peat soil, , peanut